Utilizing the program impact pathways framework for improving COVID-19 vaccine confidence and uptake: demonstrations of multi-sector collaboration from two geographies in Connecticut - Beaulieu, A.; LaMonaca, Katherine; Higginbottom, Jackson; Foster, Jaime; Macklin, Bernard; Muhammad, Tila; Schwartz, Elizabeth; Comerford, Beth; Santilli, Alycia; Duffany, Kathleen; Pérez‐Escamilla, Rafael (Vaccine, 2025)
Keywords: 2019-20 coronavirus outbreak; Biology; Coronavirus disease 2019 (COVID-19); Infectious disease (medical specialty); Medicine; Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2); Virology; dept.hhs

The implementation of a nutrition intervention in food pantries: the spirit of SWAP - Morales, Sofia I.; Vicente, Genesis; LaMonaca, Katherine; Rios, Jasmine; Cunningham, Shayna D.; Higginbottom, Jackson; Mathios, Erin; Werlin, Steve; Cramer, James; Santilli, Alycia; O’Connor Duffany, Kathleen (Health Promotion Practice, 2023)
Background. Food insecurity, affecting approximately 10% of the U.S. population, with up to 40% or higher in some communities, is associated with higher rates of chronic conditions and inversely associated with diet quality. Nutrition interventions implemented at food pantries are an effective strategy to increase healthy food choices and improve health outcomes for people experiencing food and nutrition insecurity. Supporting Wellness at Pantries (SWAP), a stoplight nutrition ranking system, can facilitate healthy food procurement and distribution at pantries. Purpose. Guided by the RE-AIM Framework, this study assesses the implementation and outcomes of SWAP as nutritional guidance and institutional policy intervention, to increase procurement and distribution of healthy foods in pantries. Method. Mixed-methods evaluation included observations, process forms, and in-depth interviews. Food inventory assessments were conducted at baseline and 2-year follow-up. Results. Two large pantries in New Haven, Connecticut, collectively reaching more than 12,200 individuals yearly, implemented SWAP in 2019. Implementation was consistent prepandemic at both pantries. Due to COVID-mandated distribution changes, pantries adapted SWAP implementation during the pandemic while still maintaining the ?spirit of SWAP.? One pantry increased the percentage of Green foods offered. Challenges to healthy food distribution are considered. Discussion. This study has implications for policy, systems, and environmental changes. It shows the potential for SWAP adoption at pantries, which can serve as a guide for continued healthy food procurement and advocacy. Maintaining the ?spirit of SWAP? shows promising results for food pantries looking to implement nutrition interventions when standard practice may not be possible.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hhs; peer-reviewed

Advancing health equity: an innovative program for building community engagement in research - Santilli, Alycia; LaMonaca, Katherine; Carr, Kendra; Rue, Bailee; D'Angelo, Karen; Higginbottom, Jackson; Morales, Sofia; Taylor, Marquita A.; Vicente, Genesis A.; Lin-Schweitzer, Anna; Duffany, Kathleen O'Connor (Progress in Community Health Partnerships: Research, Education, and Action, 2023)
Background: The Community Research Fellows (CRF) program seeks to mobilize New Haven residents with lower incomes or from communities of color who are educated and equipped to engage as equal partners in health research at Yale University. The training program combines curriculum-based information with 'on-the-ground' experience with Yale research projects, while building relationships between CRFs and researchers. The Community Alliance for Research and Engagement launched two consecutive cohorts of the program in 2018–2020., Objectives: To assess the effect of the CRF program on participants' knowledge of the research process and confidence to engage in research and participants' satisfaction and perspectives on the program., Methods: The evaluation of the CRF program included four components: 1) Pre- and Post- Program Surveys to assess change in confidence and self-reported knowledge. 2) Curriculum Feedback Satisfaction Survey to gauge satisfaction and make program improvements after each training session. 3) Post-Program CRF Interviews to explore their CRF experiences. 4) Research Team Surveys to assess program satisfaction and areas for improvement., Results: CRFs reported increased confidence and knowledge, personal and professional growth, and interest in community-engaged research. Overall, participants were very satisfied with each training module., Conclusions: The CRF program demonstrated that community members are well-suited, well-positioned, and eager to engage in and inform public health research. CRFs bring capacity and valuable perspective to research teams. The CRF training program offers an innovative approach to address power imbalances in research and to move towards more equitable community–university partnerships for improved health outcomes.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hhs; peer-reviewed

COVID-19 Vaccine Acceptance and Access Among Black and Latinx Communities - Balasuriya, Lilanthi; Santilli, Alycia; Morone, Jennifer; Ainooson, Jessica; Roy, Brita; Njoku, Anuli; Mendiola-Iparraguirre, Andrea; O’Connor Duffany, Kathleen; Macklin, Bernard; Higginbottom, Jackson; Fernández-Ayala, Celina; Vicente, Genesis; et al. (JAMA Network Open, 2021)
Black and Latinx communities have faced disproportionate harm from the COVID-19 pandemic. Increasing COVID-19 vaccine acceptance and access has the potential to mitigate mortality and morbidity from COVID-19 for all communities, including those most impacted by the pandemic.To investigate and understand factors associated with facilitating and obstructing COVID-19 vaccine access and acceptance among Black and Latinx communities.This community-partnered qualitative study conducted semistructured, in-depth focus groups with Black and Latinx participants from March 17 to March 29, 2021, using a secure video conferencing platform. Participants were recruited through emails from local community-based organizations, federally qualified health centers, social service agencies, the New Haven, Connecticut, Health Department, and in-person distribution of study information from community health workers. A total of 8 focus groups were conducted, including 4 in Spanish and 4 in English, with 72 participants from a diverse range of community roles, including teachers, custodial service workers, and health care employees, in New Haven, Connecticut. Data were analyzed from March 17 to July 30, 2021.Interviews were audio-recorded, transcribed, translated, and analyzed using an inductive content analysis approach. Themes and subthemes were identified on the acceptability and accessibility of the COVID-19 vaccine among participants who identified as Black and/or Latinx.Among 72 participants, 36 (50%) identified as Black, 28 (39%) as Latinx, and 8 (11%) as Black and Latinx and 56 (78%) identified as women and 16 (22%) identified as men. Participants described 3 major themes that may represent facilitators and barriers to COVID-19 vaccinations: pervasive mistreatment of Black and Latinx communities and associated distrust; informing trust via trusted messengers and messages, choice, social support, and diversity; and addressing structural barriers to vaccination access.The findings of this qualitative study may impact what health care systems, public health officials, policy makers, health care practitioners, and community leaders can do to facilitate equitable uptake of the COVID-19 vaccine. Community-informed insights are imperative to facilitating COVID-19 vaccine access and acceptance among communities hardest hit by the pandemic. Preventing the further widening of inequities and addressing structural barriers to vaccination access are vital to protecting all communities, especially Black and Latinx individuals who have experienced disproportionate death and loss from COVID-19.
73 citations (Crossref) [2023-10-31]
Keywords: Adolescent; Adult; African American; African Americans; Article; Black person; COVID-19 Vaccines; Connecticut; Female; Focus Groups; Health Services Accessibility; Hispanic; Hispanic Americans; Humans; Male; Middle Aged; Patient Acceptance of Health Care; SARS-CoV-2 vaccine; South and Central America; Trust; Young Adult; adolescent; adult; aged; community; content analysis; controlled study; coronavirus disease 2019; dept.pch; e-mail; employment; female; health auxiliary; health behavior; health care access; health care delivery; health care personnel; health care system; health center; health disparity; human; information processing; male; medical information; middle aged; outcome assessment; pandemic; patient attitude; peer-reviewed; public health service; qualitative research; risk factor; semi structured interview; social support; social worker; teacher; trust; vaccination; videoconferencing; young adult